Loss of ING4 enhances hematopoietic regeneration in multipotent progenitor cells - Georgina A. Anderson; Marco Hernandez; Carlos Alfaro Quinde; Zanshé Thompson; Vera Binder-Blaser; Alison M. Taylor; Katie L. Kathrein (PLoS ONE, 2025)
Despite its critical role in survival, many aspects of hematopoiesis remain unresolved. In the classical model of the hematopoietic program, quiescent hematopoietic stem cells (HSCs) sit at the top of the hematopoietic hierarchy, with the ability to self-renew and differentiate as needed. HSCs give rise to more proliferative progenitor cells, which possess multipotent potential, but have largely or completely lost self-renewal capabilities. Here, we have identified the tumor suppressor, Inhibitor of Growth 4 (ING4), as a critical regulator of multipotent progenitor (MPP) homeostasis. In the absence of ING4, we show that MPPs express a transcriptional program of hematopoietic activation, yet they remain quiescent with low levels of reactive oxygen species. Functionally, ING4-deficient MPPs are capable of robust regeneration following competitive bone marrow transplantation, resulting in substantially higher blood chimerism compared to wild-type MPPs. These data suggest ING4 deficiency promotes a poised state in MPPs, quiescent but transcriptionally primed for activation, and capable of converting the poised state into robust repopulation upon stress. Our model provides key tools for further identification and characterization of pathways that control quiescence and regeneration in MPPs.